A Comparison of MMSE and MoCA for Following Cognitive Performance with a Longitudinal Cohort Study. (20th December 2022) - Li, Daniel; Li, Wei
Abstract: Background: Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) are two commonly used cognitive screening and diagnostic tools. Method: At baseline, participants in the Alzheimer's Disease Neuroimaging Initiative (ADNI) were divided into four groups based on their cognitive diagnoses: healthy control (HC), early mild cognitive impairment (EMCI), late mild cognitive impairment (LMCI), and Alzheimer's Disease (AD). MMSE or MoCA scores were compared among the four groups using one‐way analysis of variance (ANOVA) model with post‐hoc Bonferroni correction. For those participants who had both MMSE and MoCA assessments done, a Pearson correlation analysis was performed between the two assessments for each visit. Result: The MMSE scores were significantly different among the four groups at baseline, which was true for each of the three annual follow‐up visits. By contrast, the MoCA scores were not significantly different between HC and EMCI groups at either baseline or any of the follow‐up visits. For participants with a diagnosis of LMCI, the cognitive performance deteriorated in a linear manner 12 months after the baseline, which was independent of MMSE or MoCA. At last, the MMSE scores were moderately related to MoCA scores, which got stronger along with the time of follow‐up. Conclusion: MMSE and MoCA are comparable as cognitive assessment tools to monitor cognitive changes. In addition, the measurements of MMSE and MoCA are moderately correlated for the follow‐up visits.